(untitled) (Bangladesh Journal of Botany, 2012)
Diversity, distribution and density of estuarine phytoplankton from nine sites under four Ranges of the Sundarban Mangrove Forests (SMF), Bangladesh have been studied. The phytoplankton communities represented by 36 species which belonged to Chlorophyceae (3), Euglenophyceae (2), Bacillariophyceae (30) and Xanthophyceae (1). Occurrence of taxa and their densities were highest near the confluence of Hangsha River (R) with the river Murdat at Patcosta. Shannon-Wiener diversity index was also highest (H = 3.494) in this area. Lowest density of phytoplankton and diversity indices (H = 1.661) were found in Bal R., Bisandri Khal and Kalabogi R. Oocystis pusilla, Coscinodiscus excentricus, C. lineatus and Navicula brekkeansis occurred abundantly, while Cyclotella comta, Thalassionema nitzschioides and Lioloma delicatula were common. Coscinodiscus lineatus was distributed in all the nine sites including high and low tides indicating its high capacity to tolerate habitat fluctuations. Chaetoceros socialis was found only in Passur R. with low salinity, conductivity and total dissolved solids. The total numbers of phytoplankton individuals per liter were generally higher during low tide than those of high one. Principal Component Analysis (PCA) showed the relationship between pH and some species of phytoplankton DOI: http://dx.doi.org/10.3329/bjb.v41i1.11086 Bangladesh J. Bot. 41(1): 87-95, 2012 (June)